2021
DOI: 10.3390/ijms22105096
|View full text |Cite
|
Sign up to set email alerts
|

An Eco-Friendly Approach to the Control of Pathogenic Microbes and Anopheles stephensi Malarial Vector Using Magnesium Oxide Nanoparticles (Mg-NPs) Fabricated by Penicillium chrysogenum

Abstract: The discovery of eco-friendly, rapid, and cost-effective compounds to control diseases caused by microbes and insects are the main challenges. Herein, the magnesium oxide nanoparticles (MgO-NPs) are successfully fabricated by harnessing the metabolites secreted by Penicillium chrysogenum. The fabricated MgO-NPs were characterized using UV-Vis, XRD, TEM, DLS, EDX, FT-IR, and XPS analyses. Data showed the successful formation of crystallographic, spherical, well-dispersed MgO-NPs with sizes of 7–40 nm at a maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 99 publications
1
30
0
1
Order By: Relevance
“…Similarly, Fouda and coauthors reported the potency of the bio-synthesized MgO-NPs against different pupal and larvae instar of Anopheles stephensi , with LC 50 values at 16.5 μg mL −1 for pupa and 12.5–15.5 μg mL −1 for I–IV larvae instar ( Fouda et al, 2021a ). Adesuji and coworkers reported the larvicidal efficiency of biosynthesized Ag-NPs against different instar larva phases of Culex quinquefasciatus (vector of lymphatic filariasis), recording the LC 50 and LC 90 values of 4.43 and 8.37 μg mL −1 , respectively ( Adesuji et al, 2016 ).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, Fouda and coauthors reported the potency of the bio-synthesized MgO-NPs against different pupal and larvae instar of Anopheles stephensi , with LC 50 values at 16.5 μg mL −1 for pupa and 12.5–15.5 μg mL −1 for I–IV larvae instar ( Fouda et al, 2021a ). Adesuji and coworkers reported the larvicidal efficiency of biosynthesized Ag-NPs against different instar larva phases of Culex quinquefasciatus (vector of lymphatic filariasis), recording the LC 50 and LC 90 values of 4.43 and 8.37 μg mL −1 , respectively ( Adesuji et al, 2016 ).…”
Section: Resultsmentioning
confidence: 88%
“…The inhibition percentages were 75.7%, 94.5%, and 96.1% for size 2145.9, 47.3, and 35.9 nm, respectively ( Huang et al, 2005 ). Moreover, spherical MgO-NPs synthesized through harnessing metabolites of Penicillium chrysogenum exhibited a size range of 7–40 nm and showed inhibition activity against pathogenic Gram-positive bacteria, Gram-negative bacteria, and unicellular fungi as well against larvae and pupa of malarial vector Anopheles stephensi ( Fouda et al, 2021a ). The obtained size (3.0–18.0 nm) of MgO-NPs in the current study is expected to have high activity for various biomedical and biotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment was achieved in glass vials covered with wire-Gaz lids under the previous optimum conditions required for the growth of Agrotis ipsilon. The experiment was done in triplicate, and larval mortality percentages were calculated after 72 h of treatment using the following equation [88].…”
Section: Bioassaymentioning
confidence: 99%
“…Furthermore, the resistance of insects and pests is increased due to the excessive usage of these chemical compounds. Therefore, the development of new compounds to modifying, destroying, and/or repellence of specific insects or pests are taking more attention from researchers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%